The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/1947601911432496
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Molecular Pathways of Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is an aggressive breast cancer subtype with a high rate of proliferation and metastasis, as well as poor prognosis for advanced-stage disease. Although TNBC was previously classified together with basal-like and BRCA1/2-related breast cancers, genomic profiling now shows that there is incomplete overlap, with important distinctions associated with each subtype. The biology of TNBC is still poorly understood; therefore, to define the relative contributions of major cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…Furthermore, gene analysis showed that TNBC has a defined molecular signature and is regulated by the angiotensinogen molecular network, NF-κB, platelet-derived growth factor receptor, and p53 pathways, which are important in angiogenesis, cell-cycle regulation, and inflammation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gene analysis showed that TNBC has a defined molecular signature and is regulated by the angiotensinogen molecular network, NF-κB, platelet-derived growth factor receptor, and p53 pathways, which are important in angiogenesis, cell-cycle regulation, and inflammation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from gene expression profiling analysis revealed that the nuclear factor (NF)-jB pathway may represent a key regulator of TNBC (Ossovskaya et al, 2011). Activation of NF-jB signaling has been strongly implicated in the pathogenesis of certain TNBCs (Barbie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TNBC is typically an aggressive cancer type displaying high rates of proliferation and metastasis and having generally poorer prognosis, particularly among those with advanced disease, as evidenced by increased recurrence and mortality compared with other breast cancer types [2]. Due to the lack of known therapeutic targets, such as ER, PR, and HER2 receptors, there are no specific therapies for TNBC tumors [3].…”
Section: Introductionmentioning
confidence: 99%